POTRET KEWIRAUSAHAAN PETANI PEMBUDIDAYA RUMPUT LAUT DI DESA RANDUSANGA KULON KECAMATAN BREBES KABUPATEN BREBES - Rakhmi Wijaya Ningsih; Pujiati Utami; Dumasari Dumasari (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2016)
This research was aimed to know the entrepreneurship frame of seaweed farmers in Randusanga Kulon Village, Brebes Subdistrict, Brebes Regency related with the production technique, economic aspect and post production. This research used a case study method.The sampling technique was by purposive sampling. The consideration of the sampling technique was due to the seaweed farmer swho lived and had the fish pondin Randusanga Kulon Village. The results of research include (1) the entrepreneurship frame of seaweedfarmers related with the production technique included: (a) The farmers used the cultivation technique of seaweed using monoculture system or polyculture.(b) The farmers used simple technology. (2) The entrepreneur frame of the seaweed farmer was related to the economicfactors: (a) Financial capital of the farmers was 90% of his own. (b) The cultivation of sea weed were provitable.(c) the distribution of the sea weed was directly and indirectly. (3) The entrepreneurship frame of the sea weed cultivation was related to the post production aspectincluding:(a) 100 percent of famers did post harvest technique.(b) 100 percent of farmers didn’t processing of sea weed.